Att brännmärka en julbock: Gävlebocken som city brand - Strömberg, Per (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
In 1965, merchants built a giant yule goat next to the City Hall of Gävle as a gimmick for the city and the Christmas trade, but it was immediately burnt down by someone unknown. Since then, to burn down the yule goat has become as much traditional thing to do as it is to erect it. People learned about the yule from the repeated burning. It has become an icon for the city and a part of a city brand. But the tradition is highly depending on interactivity with the public. Today, the stage of this interactivity has been culturally up-graded to cyberspace on Internet where the Yule bock-burning is discussed. Gävle’s yule goat as a phenomenon follows the dramaturgy of "buzzing" and social interactivity which remind of guerrilla marketing strategies and the so-called Relational art of the contemporary art scene. But there are no more explicit marketing strategies than to make the giant goat available for the public as a conversation piece. The yule goat is handed over to the public. The public makes the yule goat of Gävle.